Associations between fruit and vegetable variety and low-grade inflammation in Portuguese adolescents from LabMed physical activity study - Almeida-de-Souza, Juliana (2020)
Purpose: The dietary guidelines for the consumption of a variety of fruits and vegetables have been recognized as an important factor for achieving healthy eating patterns to reduce the risk of chronic disease throughout the lifespan. Our aim is to assess the association between fruit and vegetable variety and low-grade inflammation in adolescents. Methods: This cross-sectional analysis was conducted with 412 adolescents (ages 14.4 ± 1.7 years; 52% girls). The consumption of a variety of fruits and vegetables was assessed with a food-frequency questionnaire, considering the number of individual/category of fruit or vegetable intake at least once month, and categorized into tertiles. Blood samples were collected to determine C-reactive protein (CRP), interleukin-6 (IL-6), complement component 3 (C3), and 4 (C4). We created categories of lower or higher (inflammatory state) for each biomarker, considering sex- and age-adjusted median values. Then, we computed an overall inflammatory score, by adding all points awarded wherein one point was assigned if biomarker was higher or zero if lower, and created categories of 0–1 or 2–4 biomarkers above the median. The odds ratio (OR) and 95% interval confidence (95% CI) were calculated from binary logistic regression to estimate the magnitude of association between fruit and vegetable variety and inflammatory biomarkers. Results: Adolescents with a greater variety of vegetable consumption (≥13 categories/month) had lower odds of having a higher CRP (OR 0.31, 95% CI 0.15–0.64, ptrend = 0.004) when compared to those with lower variety consumption (≤6 categories/month), independent of vegetable quantity intake. However, a greater variety of fruit consumption (≥12 categories/month) had higher odds of having a higher IL-6 (OR 4.41, 95% CI 1.67–11.71, ptrend = 0.012), C3 (OR 3.30, 95% CI 1.23–8.86, ptrend = 0.047), and inflammatory score (OR 4.90, 95% CI 1.62–14.86, ptrend = 0.017), when compared to those with lower variety consumption (≤9 categories/month), independent of fruit quantity intake, only for girls. Conclusions: The consumption of a variety of vegetables is inversely associated with lower CRP. This finding supports the current dietary guidelines regarding the consumption of a variety of vegetables. The role of fruit variety in low-grade inflammation should be further studied.